Política externa americana no pós-guerra fria : como se posicionam democratas e republicanos? - Contrera, Flávio (2017)
The starting point of this thesis is the understanding of the theoretical perspective of the new institutionalism of the rational choice that the behavior of the parties can be considered an optimal adaptation to an institutional environment. We sought to demonstrate that the American foreign policy was set up after the end of the Cold War as a game (considering one arena) or a set of games (considering multiple arenas), restricted to only two parties, within a space of competition in which they employ centripetal/moderate or centrifugal/ideological strategies in order to obtain political victories. We found that the parties sought both political victories and the manifestation of ideological positions in all arenas. These positions characterized the Democratic Party as center-liberal and the Republican Party as center-conservative in the ideological spectrum of the foreign policy. However, in specific political contexts, the parties have made ideological inflections in order to obtain only victories. These inflections can be explained by variations on the perception of external threat, on the evaluation of the presidential administration, on the degree of control of the Executive over the Legislative, on the composition of the Executive's foreign policy Office, and on the ideological alignment of public opinion. In fact, the parties presented different behaviors in each of the arenas. They were most contentious in the electoral arena than in others. This difference suggests that parties have used seemingly sub-optimal strategies. However, we demonstrate that these strategies rationally express the functions that the parties assume in each of the arenas, being an optimized response to the strategic interaction between them and the political context.